Repair of Temporal Bone Encephalocele following Canal Wall Down Mastoidectomy - Sarantis Blioskas; Ioannis Magras; Stavros Polyzoidis; Konstantinos Kouskouras; Georgios Psillas; Stamatia Dova; Konstantinos Markou (Case Reports in Otolaryngology)
We report a rare case of a temporal bone encephalocele after a canal wall down mastoidectomy performed to treat chronic otitis media with cholesteatoma. The patient was treated successfully via an intracranial approach. An enhanced layer-by-layer repair of the encephalocele and skull base deficit was achieved from intradurally to extradurally, using temporalis fascia, nasal septum cartilage, and artificial dural graft. After a 22-month follow-up period the patient remains symptom free and no recurrence is noted.